Drought Assessment Using the Standardized Precipitation Index and Its Association with Climate Anomalies in Kotabumi, West Lampung - Ismail, M Rizky; Bogireddy, Chandra; Ofrial, Siti Anugrah Mulya Putri; Tiara (Indonesian Journal of Environment and Sustainability Issues, 2025)
This study assesses drought patterns in Kotabumi, West Lampung, Indonesia, using the Standardized Precipitation Index (SPI) at 1-month, 3-month, and 12-month time scales to analyze meteorological, seasonal, and hydrological droughts from 1999 to 2017. The research also explores the relationship between drought severity and global climate anomalies, particularly El Niño and La Niña (ENSO) events. Results show that short-term droughts commonly occur during the dry season (July–October), with several months experiencing extreme drought (SPI < -2.0), such as March 2016 and May 2017. Seasonal droughts, captured through SPI-3, revealed more persistent dry periods primarily in the second half of the year. Long-term analysis suggests that years like 2002, 2006, 2015, and 2016 were marked by sustained rainfall deficits. A clear correlation was found between SPI values and ENSO phases: El Niño years were associated with negative SPI values indicating drought, while La Niña years generally exhibited positive SPI values indicating wetter conditions. These findings demonstrate the effectiveness of SPI in drought monitoring and its utility in developing early warning systems and climate adaptation strategies in drought-prone regions.